Quercetin reduces chromosome aberrations induced by atrazine in the Allium cepa test - Mastrangelo, Sabina; Tomassetti, Massimiliano; Carratù, Maria Rosaria; Evandri, Maria Grazia; Bolle, Paola (Environmental and molecular mutagenesis, 2006)
Quercetin is a widely distributed plant flavonoid possessing a variety of chemical and biological activities, including chelation, free‐radical scavenging, and antioxidant activity. Atrazine is a selective triazine herbicide that has been the subject of an international revision program for human and ecological health risks because of its persistence in the environment. In a previous study, we demonstrated that atrazine was clastogenic in the Allium cepa test. In this present study, we investigated whether quercetin affords protection from the chromosome breaks induced by atrazine. In a preliminary assay, 0.1–20 μg/ml quercetin produced no toxicity or clastogenic activity in the Allium cepa test. Subsequently, we evaluated the effects of 0.5 and 5 μg/ml quercetin on the clastogenicity of 2.5, 5.0, and 7.5 μg/l atrazine. Quercetin (0.5 μg/ml) significantly reduced the frequency of total aberrations induced by 7.5 μg/l atrazine, while both concentrations of quercetin significantly decreased the frequency of fragments induced by 7.5 μg/l atrazine. The results of this study indicate that plant flavonoids such as quercetin may protect against the genotoxic effects of atrazine. Efforts to understand the extent to which plant flavonoids influence the biological activities of genotoxicants and the mechanisms involved in the interactions could help to better discern the advantages and disadvantages of their use and to clarify their possible protective role against pollutants. Environ. Mol. Mutagen., 2006 © 2006 Wiley‐Liss, Inc.